A Case Study on Critical Success Factors of AirAsia - Mamrina, Yerkezhan; Kee, Daisy Mui Hung; Tursynbay, Aidos; A/P Jayagopal, Dravyaayajnaah; Binti Mohd Athiyah, Hanis Aribah; Muhamach, Rouslan (AIBPM Publisher, 2020)
Existing literature has frequently highlighted how important are critical success factors in an organization. In this paper, we consider how these critical success factors affect an organization. Organizational success becomes important for many companies because it is very difficult to reach it in this competitive world. This pushed the organizations to improve their structure, strategy and management, and AirAsia is not an exception. AirAsia is one of the biggest low-cost airlines in Asia. It was registered in 1993 but began its activities only in 1996. The Airline company was chosen as the best low-cost airline in the world according to Skytrax eleven times. However, there is still a need for changes and improvements for AirAsia to become better. The findings of this paper have important implications for the managers and practitioners. The implication and recommendations are presented.